Intumescent synergist for enhancing char formation and method for preparing anti-ultraviolet flame-retardant polylactic acid by using intumescent synergist

By adding the expanded synergist and piperazine pyrophosphate to polylactic acid to enhance carbon, the problem that polylactic acid cannot form a carbon layer during combustion is solved, significantly improving its flame retardant properties and carbon-forming properties, and enhancing its ultraviolet and mechanical properties.

CN120230166APending Publication Date: 2025-07-01BEIJING INST OF CLOTHING TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311853155.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-29
Publication Date
2025-07-01

AI Technical Summary

Technical Problem

Polylactic acid cannot form a carbon layer during combustion, resulting in severe dripping of combustion, limiting its application in areas with high flame retardant requirements.

Method used

By synthesizing an expanded synergistic agent that enhances carbonization, it uses ferrocene formaldehyde, tannin and aminophenylboric acid, and is added to polylactic acid and melt blended with piperazine pyrophosphate to improve the flame retardancy and carbonization properties of polylactic acid.

Benefits of technology

The flame retardant and carbon-forming properties of polylactic acid are significantly improved, the limit oxygen index can reach a maximum of 36%, and the peak heat release rate and total heat release rate are reduced during the combustion process, enhancing the resistance to UV and mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004641529150000101
    Figure BDA0004641529150000101
  • Figure BDA0004641529150000111
    Figure BDA0004641529150000111
  • Figure HDA0004641529160000011
    Figure HDA0004641529160000011
Patent Text Reader

Abstract

The invention provides an intumescent synergist for enhancing char formation and a method for preparing anti-ultraviolet flame-retardant polylactic acid by using the intumescent synergist. The polylactic acid prepared by using the intumescent synergist has excellent ultraviolet protection performance and mechanical properties, the peak heat release rate (pHRR) and the total heat release rate (THR) of the polylactic acid are further greatly reduced, the carbon residue amount is increased, and the flame retardant property is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of flame-retardant polylactic acid, and particularly relates to an intumescent synergist for enhancing char formation and a method for preparing anti-ultraviolet flame-retardant polylactic acid by using the same. Background Art

[0002] Polylactic acid (PLA) has advantages such as good biocompatibility, excellent biodegradability, and outstanding melt processability, and is considered to be one of the most promising bio-based biodegradable materials. However, the flame retardancy of PLA itself is only UL94 HB grade, and the limiting oxygen index is 21%. Due to its aliphatic polyester structure, it cannot form a carbon layer during combustion, resulting in serious dripping during combustion. This limits the application of PLA in fields with high flame retardancy requirements such as automotive interiors and electronic packaging.

[0003] Currently, the flame retardants used for polylactic acid include halogen-based, phosphorus-based, nitrogen-based, silicon-based, intumescent flame retardant systems, inorganic flame retardants, nano flame retardants, and synergistic systems containing two or more flame retardants. Although the flame retardancy of PLA can be improved, some problems also arise. Among them, adding intumescent flame retardants (IFR) to PLA can effectively improve the flame retardancy level of PLA. However, most intumescent flame retardants have problems such as a large addition amount, affecting the physical properties of the substrate, and the need to improve the flame retardancy efficiency.

[0004] In the prior art, the flame retardancy of polylactic acid is achieved by adding organically modified montmorillonite, polysilsesquioxane, carbon nanotubes, expanded graphite, etc. as synergists. However, there are still many problems such as insufficient flame retardancy, affecting the mechanical properties of polylactic acid, and an addition amount greater than 20%.

[0005] Therefore, it is necessary to further research and develop technical means for realizing the flame retardancy of polylactic acid, while ensuring the mechanical properties and biodegradability, improving the comprehensive properties such as the flame retardancy of polylactic acid, so as to enrich the application fields of polylactic acid and meet the usage requirements of people. Summary of the Invention

[0006] To solve the above problems, the present invention provides an intumescent synergist for enhancing char formation, and an intumescent synergist is synthesized by using ferrocene formaldehyde, tannic acid, and aminophenylboronic acid. Adding the intumescent synergist and piperazine pyrophosphate to polylactic acid and melt-blending to obtain polylactic acid with excellent ultraviolet protection performance and mechanical properties, and the flame retardancy and char formation are greatly improved, and the limiting oxygen index can reach up to 36% at most, obtaining an anti-ultraviolet flame-retardant polylactic acid with excellent performance.

[0007] The purpose of the present invention is to provide an intumescent synergist, which is obtained by using ferrocene formaldehyde, tannic acid, and aminophenylboronic acid as raw materials, adding them to an alkyl alcohol solvent, and reacting under a protective atmosphere.

[0008] The object of the present invention also lies in providing a preparation method of the intumescent synergist, which is obtained by using ferrocene formaldehyde, tannic acid and aminophenylboronic acid as raw materials, adding them into an alkyl alcohol solvent, and reacting under a protective atmosphere.

[0009] Another object of the present invention lies in providing the use of the intumescent synergist for preparing anti-ultraviolet flame-retardant polylactic acid.

[0010] A further object of the present invention lies in providing a preparation method of anti-ultraviolet flame-retardant polylactic acid, which uses the intumescent synergist to prepare anti-ultraviolet flame-retardant polylactic acid.

[0011] In the method, the intumescent synergist, piperazine pyrophosphate and polylactic acid are mixed and melt-blended.

[0012] The present invention has the following beneficial effects:

[0013] (1) Through reasonable structural and molecular synthesis design, the present invention uses tannic acid, 3-aminophenylboronic acid and ferrocene formaldehyde to introduce flame-retardant boron elements and amino groups, and uses nucleophilic reaction to introduce ferrocene formaldehyde, realizing an intumescent synergist that integrates a carbon source (tannic acid), a high-temperature carbonized Schiff base structure and a transition metal iron element that enhances the carbonization rate.

[0014] (2) The polylactic acid obtained by melt-blending the intumescent synergist and piperazine pyrophosphate has excellent anti-ultraviolet performance, and at the same time, its mechanical properties can be enhanced.

[0015] (3) During the combustion process of the anti-ultraviolet flame-retardant polylactic acid obtained in the present invention, the peak heat release rate (pHRR) and the total heat release rate (THR) are further significantly decreased, the char residue amount is increased, effective anti-dripping is achieved, and the limiting oxygen index can reach up to 36%, and the flame-retardant performance is greatly improved. Description of the Drawings

[0016] Figure 1 Showing the SEM diagram of TBFe of the present invention;

[0017] Figure 2 Showing the infrared spectra of TA, TA-BA and TBFe in the present invention;

[0018] Figure 3 Showing the XPS spectrum of TBFe in the present invention;

[0019] Figure 4 Showing the heat release rate curves of PLA, 10PAPP / PLA, anti-ultraviolet flame-retardant polylactic acid I (0.5TBFe / 9.5PAPP / PLA), anti-ultraviolet flame-retardant polylactic acid II (1TBFe / 9PAPP / PLA) and anti-ultraviolet flame-retardant polylactic acid III (2TBFe / 8PAPP / PLA) in the present invention;

[0020] Figure 5 Show the char residue photos after cone calorimeter test of PLA and 1TBFe / 9PAPP / PLA in the present invention;

[0021] Figure 6 Show the tensile strength comparison chart of PLA, 10PAPP / PLA, anti-ultraviolet flame-retardant polylactic acid Ⅰ (0.5TBFe / 9.5PAPP / PLA), anti-ultraviolet flame-retardant polylactic acid Ⅱ (1TBFe / 9PAPP / PLA) and anti-ultraviolet flame-retardant polylactic acid Ⅲ (2TBFe / 8PAPP / PLA) in the present invention;

[0022] Figure 7 Show the transmittance change curve of the anti-ultraviolet performance test of PLA, 10PAPP / PLA, anti-ultraviolet flame-retardant polylactic acid Ⅰ (0.5TBFe / 9.5PAPP / PLA), anti-ultraviolet flame-retardant polylactic acid Ⅱ (1TBFe / 9PAPP / PLA) and anti-ultraviolet flame-retardant polylactic acid Ⅲ (2TBFe / 8PAPP / PLA) in the present invention. Detailed implementation manners

[0023] The present invention will be described in detail below through specific implementation manners, and the features and advantages of the present invention will become clearer and more definite along with these descriptions.

[0024] The present invention provides an intumescent synergist, which is obtained by using ferrocene formaldehyde, tannic acid and aminophenylboronic acid as raw materials, adding them into an alkyl alcohol solvent, and reacting under a protective atmosphere.

[0025] Tannic acid (TA), as a new type of biomass flame retardant rich in polyhydroxy structure, has the advantages of antibacterial, anti-ultraviolet properties, non-toxicity, low price, etc., and is an excellent char former. The present invention selects bio-based tannic acid as the carbon source, introduces flame-retardant B element and functional group -NH2 through the reaction of tannic acid and aminophenylboronic acid. Further, ferrocene formaldehyde is introduced into this system through a nucleophilic reaction to realize the integration of the carbon source (tannic acid), high-temperature char-forming Schiff base structure and transition metal iron element for enhancing the char-forming rate, and enhance the char-forming of the polymer to achieve its flame retardancy and anti-dripping. This synergist can endow polylactic acid with excellent anti-ultraviolet and mechanical strengthening functions at the same time.

[0026] The aminophenylboronic acid is one or more of p-aminophenylboronic acid, m-aminophenylboronic acid and o-aminophenylboronic acid, preferably p-aminophenylboronic acid and / or m-aminophenylboronic acid, such as m-aminophenylboronic acid (3-aminophenylboronic acid).

[0027] The present invention also provides a preparation method of the intumescent synergist, which is obtained by using ferrocene formaldehyde, tannic acid and aminophenylboronic acid as raw materials, adding them into an alkyl alcohol solvent, and reacting under a protective atmosphere.

[0028] In the described method, ferrocene formaldehyde is first added to an alkyl alcohol solvent for dissolution. Under a protective atmosphere, it is heated and refluxed, and then tannic acid and aminophenylboronic acid are added, and a reaction solution is obtained after the reaction.

[0029] The molar ratio of the aminophenylboronic acid to the tannic acid is 3:(0.05 - 0.45), preferably 3:(0.1 - 0.35), and more preferably 3:(0.15 - 0.25).

[0030] The molar ratio of the aminophenylboronic acid to the ferrocene formaldehyde is 3:(1 - 6), preferably 3:(1.5 - 5), and more preferably 3:(2 - 4).

[0031] The alkyl alcohol solvent is selected from one or more of C1 - C5 alkyl alcohol solvents, preferably one or more of methanol, ethanol, propanol, and isopropanol, and more preferably ethanol.

[0032] The molar volume ratio of the ferrocene formaldehyde to the alkyl alcohol solvent is 0.03 mol:(120 - 280) mL, preferably 0.03 mol:(150 - 250) mL, and more preferably 0.03 mol:(180 - 220) mL.

[0033] The reaction temperature is 50 - 85 °C, preferably 55 - 80 °C, and more preferably 60 - 75 °C. The reaction time is 2.5 - 7 h, preferably 3 - 6 h, and more preferably 3.5 - 5 h.

[0034] After the reaction solution is cooled, post-treatment is carried out to obtain an intumescent synergist. The post-treatment includes centrifugal separation, washing, and drying.

[0035] The present invention also provides the use of the intumescent synergist for preparing anti-ultraviolet flame-retardant polylactic acid.

[0036] The present invention also provides a preparation method of anti-ultraviolet flame-retardant polylactic acid, and the anti-ultraviolet flame-retardant polylactic acid is prepared by using the intumescent synergist.

[0037] In the described method, after the intumescent synergist, piperazine pyrophosphate, and polylactic acid are mixed, melt blending is carried out, such as adding them to an internal mixer for melt blending.

[0038] Preferably, before melt blending, the intumescent synergist, piperazine pyrophosphate, and polylactic acid are dried first. The drying is carried out at 70 - 90 °C for 10 - 15 h.

[0039] The mass ratio of the polylactic acid, piperazine pyrophosphate, and intumescent synergist is 90:(5 - 9.7):(0.3 - 5), preferably 90:(7 - 9.7):(0.3 - 3), and more preferably 90:(8 - 9.5):(0.5 - 2).

[0040] Adding piperazine pyrophosphate and intumescent synergist to polylactic acid, in the cone calorimeter test, the peak heat release rate (pHRR) and the total heat release rate (THR) further decrease significantly, the char residue amount increases, and the flame retardancy and anti-dripping properties of polylactic acid are greatly improved. While improving the flame retardancy, it also improves the ultraviolet protection performance of polylactic acid and ensures the tensile strength of polylactic acid.

[0041] Within the above addition amount range, as the addition amount of the intumescent synergist increases, the pHRR and THR decrease. After adding the intumescent synergist, the limiting oxygen index increases, and when it is 90:9:1, the limiting oxygen index reaches a maximum of 36%. Adding piperazine pyrophosphate alone will cause a decrease in the tensile strength of polylactic acid. When adding the intumescent synergist at the same time, when the addition amount is 90:9:1 and above, the tensile strength can be slightly improved.

[0042] The melt blending temperature is 120 - 240 °C, preferably 140 - 220 °C, more preferably 160 - 200 °C, and the time is 2 - 10 min, preferably 3 - 8 min, more preferably 4 - 6 min. If the blending temperature is too low, the flame retardant and polylactic acid are not evenly mixed, affecting the flame retardant effect. If the blending temperature is too high, polylactic acid will degrade, affecting the mechanical properties of the composite material; similarly, if the blending time is too short, the flame retardant and polylactic acid are not evenly mixed, affecting the flame retardant effect, and if the blending time is too long, the mechanical properties will decline. Within the above temperature and blending time range, the blending effect can be good and the properties of the obtained product are not affected.

[0043] In the internal mixer, the rotor speed is 40 - 120 r / min, preferably 40 - 100 r / min, more preferably 40 - 80 r / min.

[0044] Examples

[0045] Example 1

[0046] Weigh 6.4 g of ferrocene formaldehyde and add it to 200 ml of ethanol solution. Transfer the solution to a three-necked flask and stir magnetically until completely dissolved, and place the three-necked flask in an oil bath. Raise the temperature of the oil bath to 60 °C, carry out condensation reflux, and introduce nitrogen into the reaction system to ensure the nitrogen atmosphere of the reaction system throughout the process.

[0047] Weigh 3.75 g of tannic acid (TA) and 4.1 g of 3-aminophenylboronic acid (BA) and add them to the reaction system, and keep the reaction for 4 hours.

[0048] After the reaction is completed and the solution is completely cooled, the resulting solution is centrifuged at 8000 revolutions per minute using a high-speed centrifuge, and the physically attached reaction raw materials are washed away with absolute ethanol until the supernatant is clear. Finally, the lower purple precipitate is taken and dried in a vacuum oven at 80 °C for 24 h to obtain the intumescent synergist (TBFe).

[0049] Example 2

[0050] Poly(lactic acid), piperazine pyrophosphate, and TBFe were dried in a DZF-6050 vacuum oven at 80 °C for 12 hours. Then, poly(lactic acid) (PLA, Natureworks 6202D, density 1.240 g / cm 3 )), piperazine pyrophosphate (PAPP), and TBFe were placed in a Haake-type internal mixer for melt blending. The rotor speed was 50 r / min, the blending temperature was 180 °C, and the blending time was 5 min to obtain ultraviolet-resistant flame-retardant poly(lactic acid) I (0.5TBFe / 9.5PAPP / PLA). The mass ratio of poly(lactic acid), piperazine pyrophosphate (PAPP), and TBFe was 90:9.5:0.5.

[0051] Example 3

[0052] Ultraviolet-resistant flame-retardant poly(lactic acid) II (1TBFe / 9PAPP / PLA) was prepared according to the method of Example 2, with the only difference being that the mass ratio of poly(lactic acid), piperazine pyrophosphate (PAPP), and TBFe was 90:9:1.

[0053] Example 4

[0054] Ultraviolet-resistant flame-retardant poly(lactic acid) III (2TBFe / 8PAPP / PLA) was prepared according to the method of Example 2, with the only difference being that the mass ratio of poly(lactic acid), piperazine pyrophosphate (PAPP), and TBFe was 90:8:2.

[0055] Comparative Example

[0056] Comparative Example 1

[0057] Flame-retardant poly(lactic acid) (10PAPP / PLA) was prepared according to the method of Example 2, with the only difference being that TBFe was not added and the mass ratio of poly(lactic acid) to piperazine pyrophosphate (PAPP) was 90:10.

[0058] Comparative Example 2

[0059] Weigh 3.75 g of tannic acid (TA) and 4.1 g of 3-aminophenylboronic acid (BA) and add them to 200 ml of an ethanol solution. Transfer to a three-necked flask and stir magnetically until completely dissolved. Place the three-necked flask in an oil bath, raise the temperature to 60 °C, carry out condensation reflux, and introduce nitrogen into the reaction system to ensure a nitrogen atmosphere in the reaction system throughout. Maintain the reaction for 4 hours.

[0060] After the reaction was completed and the solution was completely cooled, the resulting solution was centrifuged at 8000 revolutions using a high-speed centrifuge, and the physically attached reaction raw materials were washed away with absolute ethanol until the supernatant was clear. Finally, the lower-layer precipitate was taken and dried in a vacuum oven at 80 °C for 24 h to obtain the product TA-BA.

[0061] Experimental Example

[0062] Experimental Example 1

[0063] Scanning electron microscopy (SEM) test was carried out on TBFe, specifically as Figure 1 shown. It can be seen from the SEM characterization that the microscopic morphology of the TBFe flame retardant presents regular nano-spheres, and the average particle size is about 220 nm.

[0064] Experimental Example 2

[0065] Infrared test was carried out on TA, TA-BA and TBFe, and the specific infrared spectra are as Figure 2 shown.

[0066] It can be seen from the infrared test characterization that after the reaction of tannic acid with 3-aminophenylboronic acid, the amino group was successfully introduced. After reacting with the aldehyde group of ferrocene formaldehyde, the amino peak disappeared and a C=N double bond was formed, indicating the successful preparation of the TBFe flame retardant.

[0067] It is reasonably speculated that the boronic acid group of 3-aminophenylboronic acid reacts with the hydroxyl group in tannic acid, and the amino group of 3-aminophenylboronic acid reacts with the aldehyde group in ferrocene formaldehyde to obtain TBFe.

[0068] Tannic acid (TA), as a new type of biomass flame retardant rich in polyhydroxy structure, has the characteristics of antibacterial, anti-ultraviolet, non-toxic, low cost, etc. It is an excellent charring agent. The flame retardant B element and functional group -NH2 are introduced by the reaction of tannic acid with 3-aminophenylboronic acid. Further, ferrocene formaldehyde is introduced into this system through a nucleophilic reaction to realize the integration of the carbon source (tannic acid), the high-temperature charring Schiff base structure and the transition metal iron element that can enhance the charring rate, and enhance the carbonization of the polymer to achieve its flame retardancy and anti-dripping. In addition, the structural design of this synergist can endow polylactic acid with excellent anti-ultraviolet and mechanical enhancement functions at the same time.

[0069] Experimental Example 3

[0070] X-ray photoelectron spectroscopy (XPS) test was carried out on TBFe, and the test results are as Figure 3 shown. It can be seen from the XPS test characterization that key elements such as Fe, B, and N appear in the TBFe flame retardant.

[0071] Experimental Example 4

[0072] The limiting oxygen index and anti-dripping tests were carried out on polylactic acid PLA, 10PAPP / PLA, anti-ultraviolet flame-retardant polylactic acid Ⅰ (0.5TBFe / 9.5PAPP / PLA), anti-ultraviolet flame-retardant polylactic acid Ⅱ (1TBFe / 9PAPP / PLA), and anti-ultraviolet flame-retardant polylactic acid Ⅲ (2TBFe / 8PAPP / PLA). The test results are shown in Table 1.

[0073] Table 1

[0074] Sample Name UL-94 Rating LOI (%) Drip Resistance PLA V-2 20 Large Amount of Drips 10PAPP / PLA V-2 29 Small Amount of Drips 0.5TBFe / 9.5PAPP / PLA V-2 34 Small Amount of Drips 1TBFe / 9PAPP / PLA V-0 36 No Drips 2TBFe / 8PAPP / PLA V-2 30 Small Amount of Drips

[0075] The pure polylactic acid PLA spline had no char formation and dripped, with an oxygen index value of 20%, showing flammability. Compared with 1TBFe / 9PAPP / PLA, due to the addition of the intumescent synergist (TBFe), the char formation degree and char formation rate of the functional flame-retardant polylactic acid were greatly improved, and the oxygen index was increased to 36%. 1TBFe / 9PAPP / PLA had no dripping during combustion and quickly formed char to cover the entire top of the spline. The good char layer isolated fire and heat, effectively improving the flame-retardant performance.

[0076] Experimental Example 5

[0077] The cone calorimeter test was carried out on polylactic acid PLA, 10PAPP / PLA, anti-ultraviolet flame-retardant polylactic acid Ⅰ (0.5TBFe / 9.5PAPP / PLA), anti-ultraviolet flame-retardant polylactic acid Ⅱ (1TBFe / 9PAPP / PLA), and anti-ultraviolet flame-retardant polylactic acid Ⅲ (2TBFe / 8PAPP / PLA). The test was carried out using a standard cone calorimeter (FTT Standard CornCalorimeter) from Fire Testing Technology Ltd in the UK, with a heat radiation power of 35 kW / m 2 , the sample size was 100 mm × 100 mm × 3 mm, and the test standard was carried out according to ISO 5660-1 "Fire Reaction Tests - Heat Release, Smoke Production and Mass Loss Rate - Part 1: Heat Release Rate (Cone Calorimeter Method)".

[0078] The pHRR, THR, and Char test results are shown in Table 2, and the heat release rate curve is as Figure 4 shown, and the char residue photos of PLA and 1TBFe / 9PAPP / PLA after the cone calorimeter test are as Figure 5 shown.

[0079] Table 2

[0080]

[0081]

[0082] The addition of PAPP and TBFe significantly reduced the heat release rate of the polylactic acid material. Compared with PLA, the peak heat release rate (pHRR) of 1TBFe / 9PAPP / PLA decreased by 46.5%, and the heat release rate remained low for a long time. Moreover, the total heat release rate (THR) was effectively reduced (by 25.1%), showing excellent flame retardancy, and the char residue increased to 18.60%.

[0083] The char residue photos after the cone calorimeter test of polylactic acid and 1TBFe / 9PAPP / PLA show that there is almost no residue in pure polylactic acid, while 1TBFe / 9PAPP / PLA enhances the charring ability of polylactic acid, and the expanded char layer completely covers the entire sample, indicating its excellent charring ability.

[0084] Experimental Example 6

[0085] Tensile strength tests were carried out on polylactic acid PLA, 10PAPP / PLA, anti-ultraviolet flame-retardant polylactic acid I (0.5TBFe / 9.5PAPP / PLA), anti-ultraviolet flame-retardant polylactic acid II (1TBFe / 9PAPP / PLA), and anti-ultraviolet flame-retardant polylactic acid III (2TBFe / 8PAPP / PLA), and the tensile strength comparison is Figure 6 as shown. A tensile tester (INSTRON5966) from INSTRON Corporation, USA was used to test the tensile strength and elastic modulus of the specimens. The gauge length of the specimens was 25 mm, the tensile rate was 10 mm / min, and the test was carried out according to GB / T1040-1992.

[0086] The addition of PAPP decreased the tensile strength of polylactic acid by 13%, while the addition of TBFe gradually increased it. Compared with PAPP / PLA, the tensile strength of 2TBFe / 8PAPP / PLA increased by 23%.

[0087] Experimental Example 7

[0088] Anti-ultraviolet performance tests were carried out on polylactic acid PLA, 10PAPP / PLA, anti-ultraviolet flame-retardant polylactic acid I (0.5TBFe / 9.5PAPP / PLA), anti-ultraviolet flame-retardant polylactic acid II (1TBFe / 9PAPP / PLA), and anti-ultraviolet flame-retardant polylactic acid III (2TBFe / 8PAPP / PLA), and the test results are Figure 7 as shown. A double-beam ultraviolet-visible reflection spectrophotometer (UV-3600, Shimadzu Corporation, Japan) was used to measure the ultraviolet transmittance of the polylactic acid film (thickness 0.2 mm) to characterize the anti-ultraviolet performance.

[0089] Under the combined action of PAPP and TBFe, the anti-ultraviolet flame-retardant polylactic acids Ⅰ (0.5TBFe / 9.5PAPP / PLA), Ⅱ (1TBFe / 9PAPP / PLA) and Ⅲ (2TBFe / 8PAPP / PLA) exhibit excellent ultraviolet protection effects.

[0090] The anti-ultraviolet performance of polylactic acid is greatly improved after adding PAPP (10PAPP / PLA). The addition of TBFe further enhances the ultraviolet protection performance, especially in the wavelength range greater than 375nm. Among them, the test curves of 0.5TBFe / 9.5PAPP / PLA and 1TBFe / 9PAPP / PLA are basically coincident. The protection effect of 2TBFe / 8PAPP / PLA is the best, and the transmittance (Transmittance%) is the lowest, achieving high-efficiency anti-ultraviolet performance in the full ultraviolet band.

[0091] The present invention has been described in detail above in combination with specific embodiments and / or exemplary examples and the accompanying drawings. However, these descriptions should not be construed as limiting the present invention. Those skilled in the art understand that without departing from the spirit and scope of the present invention, various equivalent substitutions, modifications or improvements can be made to the technical solutions and their implementation manners of the present invention, and these all fall within the scope of the present invention. The protection scope of the present invention shall be subject to the appended claims.

Claims

1. An intumescent synergist is obtained by using ferrocene formaldehyde, tannic acid and aminophenylboronic acid as raw materials, adding them into an alkyl alcohol solvent and reacting under a protective atmosphere.

2. The intumescent synergist according to claim 1, characterized in that The aminophenylboronic acid is one or more of p-aminophenylboronic acid, m-aminophenylboronic acid and o-aminophenylboronic acid.

3. The intumescent synergist according to claim 1, characterized in that the molar ratio of the aminophenylboronic acid to tannic acid is 3:(0.05 - 0.45), preferably 3:(0.1 - 0.35), more preferably 3:(0.15 - 0.25), the molar ratio of the aminophenylboronic acid to ferrocene formaldehyde is 3:(1 - 6), preferably 3:(1.5 - 5), more preferably 3:(2 - 4).

4. The intumescent synergist according to claim 1, wherein The reaction temperature is 50 - 85 °C, preferably 55 - 80 °C, more preferably 60 - 75 °C.

5. A preparation method of an intumescent synergist, characterized in that, It is obtained by using ferrocene formaldehyde, tannic acid and aminophenylboronic acid as raw materials, adding them into an alkyl alcohol solvent and reacting under a protective atmosphere.

6. A preparation method of ultraviolet-resistant and flame-retardant polylactic acid, characterized in that, The method uses the intumescent synergist according to any one of claims 1 to 4 to prepare an anti-ultraviolet and flame-retardant polylactic acid.

7. The method according to claim 6, wherein In the method, the intumescent synergist, piperazine pyrophosphate and polylactic acid are mixed and then melt-blended.

8. The method according to claim 7, wherein Before melt-blending, the intumescent synergist, piperazine pyrophosphate and polylactic acid are dried first.

9. The method according to claim 7, wherein The mass ratio of the polylactic acid, piperazine pyrophosphate and intumescent synergist is 90:(5 - 9.7):(0.3 - 5), preferably 90:(7 - 9.7):(0.3 - 3), more preferably 90:(8 - 9.5):(0.5 - 2).

10. The method according to claim 7, characterized in that, The melt blending temperature is 120 - 240 °C, preferably 140 - 220 °C, more preferably 160 - 200 °C, and the time is 2 - 10 min, preferably 3 - 8 min, more preferably 4 - 6 min.